Efficacy of Chloral Hydrate-Hydroxyzine and Chloral Hydrate-Midazolam in Pediatric Magnetic Resonance Imaging Sedation - FALLAH, Razieh; FADAVI, Nafiseh; BEHDAD, Shekofah; FALLAH TAFTI*, Mohammad (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Fallah R, Fadavi N, Behdad Sh, Fallah Tafti M. Efficacy of Chloral Hydrate-Hydroxyzine and Chloral Hydrate-Midazolam in Pediatric Magnetic Resonance Imaging Sedation. Iran J Child Neurol. 2014 Spring 8(2):11-17. Objective Magnetic resonance imaging (MRI) is a useful diagnostic tool for the evaluation of congenital or acquired brain lesions. But, in all of less than 8-year-old children, pharmacological agents and procedural sedation should be used to induce motionless conditions for imaging studies. The purpose of this study was to compare the efficacy and safety of combination of chloral hydrate-hydroxyzine (CH+H) and chloral hydrate-midazolam (CH+M) in pediatric MRI sedation. Materials & Methods In a parallel single-blinded randomized clinical trial, sixty 1-7-year-old children who underwent brain MRI, were randomly assigned to receive chloral hydrate in a minimum dosage of 40 mg/kg in combination with either 2 mg/kg of hydroxyzine or 0.5 mg/kg of midazolam. The primary outcomes were efficacy of adequate sedation (Ramsay sedation score of five) and completion of MRI examination. The secondary outcome was clinical side-effects. Results Twenty-eight girls (46.7%) and 32 boys (53.3%) with the mean age of 2.72±1.58 years were studied. Adequate sedation and completion of MRI were achieved in 76.7% of CH+H group. Mild and transient clinical side-effects, such as vomiting of one child in each group and agitation in 2 (6.6 %) children of CH+M group, were also seen. The adverse events were more frequent in CH+M group. Conclusion Combinations of chloral hydrate-hydroxyzine and chloral hydrate-midazolam were effective in pediatric MRI sedation; however, chloral hydrate-hydroxyzine was safer. References 1. Lehman RK, Schor NF. Neurologic Evaluation. In:Kliegman RM, Stanton BF, Schor NF, St. Geme JW,Behrman RE, editors. Nelson Textbook of Pediatrics.19th ed. Philadelphia: Saunders; 2011. p. 2013-7. 2. Sahyoun C, Krauss B. Clinical implications of pharmacokinetics and pharmacodynamics of procedural sedation agents in children. Curr Opin Pediatr 2012;24:225-32. 3. Mason KP, Prescilla R, Fontaine PJ, Zurakowski D. Pediatric CT sedation: comparison of dexmedetomidine and pentobarbital. AJR Am J Roentgenol 2011;196(2):W194-8. 4. Schulte-Uentrop L, Goepfert MS. Anaesthesia or sedation for MRI in children. Curr Opin Anaesthesiol 2010;23(4):513-7. 5. Freeman JM. The risks of sedation for electroencephalograms: data at last. Pediatrics 2001; 108(1):178. 6. Cortellazzi P, Lamperti M, Minati L, Falcone C, Pantaleoni C, Caldiroli D. Sedation of neurologically impaired children undergoing MRI: a sequential approach. Paediatr Anaesth 2007;17(7):630-6. 7. Haselkorn T, Whittemore AS, Udaltsova N, Friedman GD. Short-term chloral hydrate administration and cancer in humans. Drug Saf 2006; 29(1):67-77. 8. Costa LR, Costa PS, Brasileiro SV, Bendo CB, Viegas CM, Paiva SM. Post-Discharge Adverse Events following Pediatric Sedation with High Doses of Oral Medication. J Pediatr 2012;160(5):807-13. 9. da Costa LR, da Costa PS, Lima AR. A randomized double-blinded trial of chloral hydrate with or without hydroxyzine versus placebo for pediatric dental sedation. Braz Dent J 2007;18(4):334-40. 10. Klein EJ, Brown JC, Kobayashi A, Osincup D, Seidel K. A randomized clinical trial comparing oral, aerosolized intranasal, and aerosolized buccal midazolam. Ann Emerg Med 2011;58(4):323-9. 11. Johnson E, Briskie D, Majewski R, Edwards S, Reynolds P. The physiologic and behavioral effects of oral and intranasal midazolam in pediatric dental patients. Pediatr Dent 2010;32(3):229-38. 12. Wetzel RC. Anesthesia, Perioperative Care, and Sedation. In: Kliegman RM, Stanton BF, Schor NF, St. Geme JW, Behrman RE, editors. Nelson Textbook of Pediatrics. 19th ed. Philadelphia: Saunders; 2011. p. 359-60. 13. Cote CJ, Wilson S. Guidelines for monitoring and management of pediatric patients during and after sedation for diagnostic and therapeutic procedures: an update. Pediatrics 2006;118(6):2587-602. 14. Ramsay MA, Savege TM, Simpson BR, Goodwin R. Controlled sedation with alphaxalone-alphadolone. Br Med J 1974;2(5920):656-9. 15. Fallah R, Jalili Sh, Golestan M, Akhavan Karbasi S, Jarahzadeh MH. Efficacy of chloral hydrate and promethazine for sedation during electroencephalography in children; a randomised clinical trial. Iran J Pediatr 2013;23(1):27-31. 16. Fallah R, Nakhaei MH, Behdad S, Moghaddam RN, Shamszadeh A. Oral chloral hydrate vs. intranasal midazolam for sedation during computerized tomography. Indian Pediatr 2013;50(2):233-5. 17. Mason KP, Sanborn P, Zurakowski D, Karian VE, Connor L, Fontaine PJ, et al. Superiority of pentobarbital versus chloral hydrate for sedation in infants during imaging. Radiology 2004;230(2):537-42. 18. Chowdhury J, Vargas KG. Comparison of chloral hydrate, meperidine, and hydroxyzine to midazolam regimens for oral sedation of pediatric dental patients. Pediatr Dent 2005;27(3):191-7. 19. Roach CL, Husain N, Zabinsky J, Welch E, Garg R.Moderate sedation for echocardiography of preschoolers. Pediatr Cardiol 2010;31(4):469-73. 20. Avalos-Arenas V, Moyao-García D, Nava-Ocampo AA, Zayas-Carranza RE, Fragoso-Ríos R. Is chloral hydrate/ hydroxyzine a good option for paediatric dental outpatient sedation? Curr Med Res Opin 1998;14(4):219-26. 21. Torres-Pérez J, Tapia-García I, Rosales-Berber MA, Hernández-Sierra JF, Pozos-Guillén Ade J. Comparison of three conscious sedation regimens for pediatric dental patients. J Clin Pediatr Dent 2007;31:183-6. 22. Lee YJ, Kim do K, Kwak YH, Kim HB, Park JH, Jung JH. Analysis of the appropriate age and weight for pediatric patient sedation for magnetic resonance imaging. Am J Emerg Med 2012;30(7):1189-95. 23. Kannikeswaran N, Sethuraman U, Sivaswamy L, Chen X, Mahajan PV. Children with and without developmental disabilities: sedation medication requirements and adverse events related to sedation. Pediatr Emerg Care 2012;28(10):1036-40. 24. Fávero ML, Ponce FA, Pio MR, Tabith Junior A, Carvalho e Silva FL. Chloral hydrate to study auditory brainstem response. Braz J Otorhinolaryngol 2010;76(4):433-6. [Article in English, Portuguese] 25. Heistein LC, Ramaciotti C, Scott WA, Coursey M, Sheeran PW, Lemler MS. Chloral hydrate sedation for pediatric echocardiography: physiologic responses, adverse events, and risk factors. Pediatrics 2006;117(3):e434-41.